Bantuan Hukum Bagi Masyarakat Pra Sejahtera Dalam Penegakan HAM - Munawir, Zaini; Harahap, Herlina Hanum; Fatmawati, Eka (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Legal aid for underprivileged communities is important to protect and enforce human rights. This effort aims to recognize and respect individual rights by providing free legal services by advocates to underprivileged clients. This study explores the role of legal aid in the enforcement of human rights and justice in Indonesia. Qualitative methods with a conceptual approach are used to analyze legal substance, relying on secondary and tertiary data. It is important to understand the challenges in access to justice, even though human rights protection and constitutional rights are already in place. The implementation of legal aid still faces challenges that require improvement so that fair and effective access can be fulfilled for all individuals, especially those in need. This research aims to strengthen the concept of legal aid to ensure better protection of human rights.